Back to base pairs: What is the genetic risk for red bloodcell alloimmunization?. (July 2021) - Gerritsma, J.J.; Oomen, I.; Meinderts, S.; van der Schoot, C.E.; Biemond, B.J.; van der Bom, J.G.; Fijnvandraat, K.; van Beers, E.J.; Biemond, B.J.; Beijlevelt, M.; Brons, P.P.T.; et al.
Abstract: Red blood cell (RBC) alloimmunization is a serious complication of blood transfusions, challenging selection of compatible units for future transfusions. Genetic characteristics may be associated with the risk of RBC alloimmunization and may therefore serve to identify high-risk patients. The aim of this systematic review was to summarize the available evidence on genetic risk factors for RBC alloimmunization. Electronic databases were searched up to April 2020 for studies (Search terms included transfusion, alloimmunization and genetic). A total of 2581 alloimmunized cases and 26, 558 controls were derived from 24 studies. The alleles that were most frequently studied and that demonstrated significant associations in a meta-analysis with alloimmunization to the Duffy a antigen were HLA-DRB1*04 (Odds Ratio 7.80 (95%CI 4.57–13.33)), HLA-DRB1*15 (OR 3.76 (95%CI 2.14–6.59)), and HLA-DRB1*03 (OR 0.12 (95%CI 0.05–0.29)). Furthermore, significant associations with anti-K formation was found for the alleles HLA-DRB1*10 (OR 2.64 (95%CI 1.41–4.95)), HLA*DRB1*11 (OR 2.11, (95%CI 1.34–3.32)), and HLA-DRB1*13 (OR 1.71 (95%CI 1.26–2.33)). Overall, the available evidence was of moderate to low quality, hampering interpretation of reported results. There is an urgent need for high quality evidence on genetic risk factors for RBC alloimmunization. Highlights: RBC alloimmunization is a serious complication of transfusions, challenging selection of units for future transfusions. Several HLA-DRB1 alleles are associated with alloimmunization to the Fy a and K antigen. Prevention of RBC alloimmunization requires a robust risk assessment, including genetic and clinical markers.